Does Gender Matter in Septic Patient Outcomes?. Issue 4 (2nd April 2019) - Failla, Kim Reina; Connelly, Cynthia D.; Ecoff, Laurie; Macauley, Karen; Bush, Ruth
Abstract: Purpose: The purpose of this study was to examine potential gender disparities in relation to factors associated with sepsis management among a cohort of patients admitted through an emergency department with a discharge diagnosis of severe sepsis or septic shock. Sepsis is one of the leading causes of death globally, with significant associated costs. Predictors of survival for those with sepsis‐related diagnoses are complex. Design and Methods: The study had a retrospective, descriptive cross‐sectional design. The sample ( N = 482) included patients 18 years of age or older who presented to the emergency department of a nonprofit, Magnet‐recognized, acute care hospital located in southern California. Subjects included those who subsequently met the criteria for a discharge diagnosis of severe sepsis or septic shock as defined by the Surviving Sepsis Campaign. Patient characteristics, clinical variables, care management processes, and outcomes were extracted from the electronic health record. A multivariate model was analyzed. Findings: The sample included 234 women (48.5%) and 248 men (51.5%). Logistic regression with eight independent variables (discharge diagnosis, age, comorbidities, length of hospital stay, source of infection, first serum lactate level measured, recommended fluids administered, and gender) reliably predicted odds for patient survival, ϰ 2 (12) = 118.38, p < .001, and correctly classified 77.3% of cases. All eight independent variables significantly contributed to the model. Men had a higher likelihood of hospital survival than women (odds ratio 1.68; 95% confidence interval 1.01–2.79; p = .045). Conclusions: The Surviving Sepsis Campaign has provided a clear pathway for care of patients with sepsis‐related diagnoses. Therapeutic strategies should be developed to address differences in outcome by gender. The adoption of more aggressive applications of evidence‐based interventions for these patients may result in better patient outcomes. Clinical Relevance: Providers should understand the importance of adhering to sepsis protocols, minimizing treatment disparities, and recognizing gender differences.